2007
DOI: 10.17660/actahortic.2007.738.101
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of the 2s Albumin Gene and Promoter From Grapevine

Abstract: High-throughput sequencing of cDNA libraries has resulted in millions of expressed sequence tags (ESTs) from plants. To exploit such a valuable molecular resource for functional analysis of genes and genetic elements, we developed an improved thermal asymmetric interlaced (TAIL) PCR technique. We demonstrated its usefulness by recovering the complete seed-specific 2S albumin gene and promoter using a partial EST and genomic DNA of Vitis vinifera grapevine. The 2S albumin VvAlb1 (V. vinifera 2S albumin 1) gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
(26 reference statements)
0
3
0
Order By: Relevance
“…For the sake of acquirement of gapdh promoter and terminator sequences, as well as further elucidation of gapdh genomic structure, we isolated the full-length gapdh genomic sequence based on its cDNA information. TaKaRa genome walking technique enables these aims relying on thermal asymmetric interlaced PCR (TAIL-PCR), 20 which requires application of three sequential nested PCRs using a set of gene-specific primers (SPs) in combination with asymmetric primer (AP) of lower Tm as compared to SPs (Figure 3). Through these manipulations, we can obtain upstream and downstream sequences flanking the known sequence, such as promoter and terminator, and other regulatory sequences.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…For the sake of acquirement of gapdh promoter and terminator sequences, as well as further elucidation of gapdh genomic structure, we isolated the full-length gapdh genomic sequence based on its cDNA information. TaKaRa genome walking technique enables these aims relying on thermal asymmetric interlaced PCR (TAIL-PCR), 20 which requires application of three sequential nested PCRs using a set of gene-specific primers (SPs) in combination with asymmetric primer (AP) of lower Tm as compared to SPs (Figure 3). Through these manipulations, we can obtain upstream and downstream sequences flanking the known sequence, such as promoter and terminator, and other regulatory sequences.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The expression vectors were transformed into Agrobacterium tumefaciens EHA105 by the freeze‐thaw method (Gai et al., ). The foreign genes were then transfected into wild‐type tobacco NC89 using leaf disc transformation (Li, Qi, Shu, Zheng, & Li, ). T 2 transgenic tobacco plants which over‐expressed the TaIRI4 or TaIRI6 were subjected to screening.…”
Section: Methodsmentioning
confidence: 99%
“…The 1216 bp promoter sequence of chitinase gene VCH3 (GenBank accession number AF441123) was isolated and the transcriptional start site was identified by primer extension analysis [23]. Sequence analysis revealed that the VCH3 promoter contains two inverse SA cis-acting elements (TGACG) located at −293 and −1181 bp relative to the transcriptional start site (Fig.…”
Section: Promoter Elements In the Vch3 Promoter And Generation Of Sitmentioning
confidence: 99%